(untitled) (Research Announcements "Heritage BG", 2025)
This paper investigates what motives drive visitors to travel to sites of cultural heritage. It uses a case study on five out of many heritage sites in the Shumen city area, where quantitative questionnaires with visitors were fielded (100 at each site). It traces the motivation of visitors from the channels of awareness about cultural heritage through their visit on site, and repeated visitation to the same site. The study finds out that regardless how important a heritage site is, when history is combined with an experience in attractive nature surroundings a repeated visitation is more probable. The data further indicates that for the first visit to a site, it is the demand for more knowledge about history that is the primary driving force. Knowledge induces personal identity, which is particularly seen in the motives of parents and grandparents who, regardless whether they come for the first or second time, come to get their children acquainted with their heritage. The need for knowledge experience runs through the time people spent at a site, sometimes with a night spent in the city during the trip. Typically, they visit one or two heritage places at a maximum, but leave with the determination to come back again to enjoy the other sites in the area. References: Dai et al. 2019: Dai, Tianchen, Hein, Carola, Zhang, Tong. Understanding How Amsterdam City Tourism Marketing Addresses Cruise Tourists’ Motivations Regarding Culture. Tourism Management Perspectives, vol. 29, 157-165. Koufodontis 2022: Koufodontis, Nikolaos Iason. UNESCO Urban World Heritage Sites: Tourists’ Awareness in the Area of Social Media. Cities, https://www.sciencedirect.com/science/article/abs/pii/S0264275122001834 [accessed May 23, 2022]. Medina-Viruel et al. 2019: Medina-Viruel, Miguel Jesus, Lopez-Guzman, Tomas, Galvez, Jesus Claudio Perez, Jara-Alba, Carol. Emotional Perception and Tourist Satisfaction in World Heritage Cities: The Renaissance Monumental Site of Ubeza and Baeza, Spain. Journal of Outdoor Recreation and Tourism, vol. 27. Murdy et al. 2018: Murdy, Samanta, Alexander, Matthew, Bryce, Derek. What Pulls Ancestral Tourist ‘Home’? An Analysis of Ancestral Tourist Motivations. Tourism Management, vol. 64, 12-19. Naipeng et al. 2021: Naipeng, (Tom) Bu, Pan, Steve, Kong, Haiyan, Fu, Xiaoxiao, Lin, Bingna Lin. Profiling Literary Tourist: A Motivational Perspective. Journal of Destination Marketing & Management, vol. 22, 100659. Niemezyk 2013: Niemezyk, Agata. Cultural Tourists: ‘An attempt to classify them’. Tourism Management Perspectives, vol. 5, 24-30. Prayag et al. 2022: Prayag, Girish, Pung, Jessica Mei, Lee, Craig, Chiappa, Giacomo Dei. The Self-concept and Psychological Antecedents of Intention to Recommend a Heritage Site: The Moderating Effect of Visitor Type. Tourism Management Perspectives, vol. 42, 100962. Vargas et al. 2021: Vargas, Elena Para, de-Juan-Ripoll, Carla, Panadero, Marta Bueno, Alcaniz, Mariano. Lifestyle Segmentation of Tourists: The Role of Personality. Heliyon, vol. 7, Issue 7, e07579. Vladimirov 2021: Vladimirov, Zhelyu. Cultural Heritage as a resource for local development 2021, Scientific News, Bulletin ‘Heritage BG’, N1, 9-15.